Grammarly as Students’ Writing Assistance to Improve Student's Essay: Exploring Students’ Perception - Suhayati, Lisa (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
Writing subject is complex since it does not only have to focus on the organization of the essay but also the mechanical factors such as grammar or sentence structures. The problem matters for both students and teachers. Students and teachers need to find help to minimize the problem in teaching and learning Essay Writing such as the use of writing tool like Grammarly. The study aims to find out the advantages of grammarly is in helping students to write their essay, the drawbacks they face in using Grammarly and students’ response toward Grammarly. This study applies descriptive qualitative method to elaborate the analysis. It engages 15 students of Essay Writing subject purposely. Moreover, the research data were collected by two instruments, i.e. interview and questionnaires. Then, the findings show that students have positive view toward Grammarly as their writing assistance in their essay writing. Moreover, Grammarly some advantages to help students in writing their essay. However, the drawbacks that students face when using Grammarly could not be neglected.